(untitled) (World Science, 2021)
Transcondylar and supracondylar fractures of the humerus in children are one of the most relevant and still not completely solved problems of modern pediatric traumatology. In the problem of condylar and supraorbital fractures of the humerus, the issues of diagnosis, choice of indications for surgical revision of the vascular-nervous bundle of the elbow area in this pathology are insufficiently covered. To solve the problems of the study, we analyzed the treatment of 313 victims with transcondylar and supracondylar fractures of the humerus, which were treated at the City Children’s Clinical Hospital in Lviv in the period from 2013 to 2018. The structure of the distribution of arrays on the basis of rotational displacement in condylar fractures of the humerus is dominated by displacement up to 30°, which in the first group was found in 61.8% of cases, and in the second group - 69.2% of cases. The share of severe rotational displacements in the structure of group arrays is almost the same in both observation groups: 29.1% in the first group and 29.5% in the second group. Analysis of the proportion of extremely severe rotational displacements up to 90° in the structure of group arrays revealed that such victims were 7 times more among the victims of the first group than among the victims of the second group, due to the use of the proposed unified protocol scheme for diagnosis and treatment humeral fractures in pediatric patients, which avoids or reduces the difference in the occurrence of secondary displacements.